PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP IPA SISWA DAN PENGELOLAAN PEMBELAJARAN GURU DENGAN MENERAPKAN MODEL PEMBELAJARAN BERBASIS MASALAH - Nurhasana Siregar (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2019)
Abstract: This action research aims to describe the understanding of students' science concepts and describe the teacher's ability to manage learning on the actual problems of learning in the classroom by applying problem-based learning models. The research subjects were students of class VII-4 totaling 44 people and 1 science teacher. This classroom action research is carried out in two cycles, each of which consists of the stages of planning, implementing actions, observation, and reflection. The results showed that the ability of students to understand the concept in the first cycle was 59.09%, and in the second cycle there was an increase with a percentage of 86.36%. While the ability of teachers in the first cycle the average score of 3.1 and in the second cycle there was an improvement in learning practices so that an increase in the average score (3.8). Keywods: concept understanding, management of learning, problem based learning